Molecular mechanism of azithromycin resistance among typhoidal Salmonella strains in Bangladesh identified through passive pediatric surveillance - Hooda, Yogesh; Sajib, Mohammad S. I.; Rahman, Hafizur; Luby, Stephen P.; Bondy-Denomy, Joseph; Santosham, Mathuram; Andrews, Jason R.; Saha, Samir K.; Saha, Senjuti (PLOS Neglected Tropical Diseases, 2019)
Author summary With the outbreak of extensively resistant (XDR) typhoid fever in Pakistan, azithromycin has become the last oral drug to treat typhoid. Although no azithromycin resistant XDR isolate has been reported to date, the increasing use of azithromycin and the clear historical record of widespread dissemination of resistance to all previously widely used antimicrobials by typhoidal Salmonella, suggest we will soon face strains resistant to all oral antibiotics. This makes it imperative to elucidate the mechanism of azithromycin resistance in typhoidal Salmonella. We tested 1,082 typhoidal Salmonella isolates from the two largest pediatric hospitals of Bangladesh and identified 13 azithromycin-resistant isolates. Using comparative genomics, we identified a mutation in a specific protein called AcrB that makes these isolates resistant to azithromycin. All azithromycin-resistant strains were susceptible to cephalosporin but resistant to all other oral antibiotics. The Pakistan outbreak strain is resistant to all common oral antibiotics and only susceptible to azithromycin. Acquisition of the plasmid that confers cephalosporin resistance in XDR strains by the Bangladeshi azithromycin-resistant strains or rise of the AcrB mutation in the XDR strains could be the end of oral treatment for typhoid. This poses serious threats to the health system of LMICs where typhoid is endemic. Currently, the majority of typhoid patients are prescribed oral treatment in the outpatient department, but an azithromycin-resistant XDR strain would shift enteric fever treatment from outpatient departments to inpatient departments to be treated with injectable antibiotics like carbapenems, further burdening already struggling health systems in endemic regions. Moreover, with the dearth of novel antimicrobials in the horizon, we risk losing our primary defense against widespread mortality from enteric fever.